Anger Can Help: A Transactional Model and Three Pathways of the Experience and Expression of Anger. Issue 3 (23rd July 2017) - Butler, Mark H.; Meloy‐Miller, Kierea C.; Seedall, Ryan B.; Dicus, J. Logan
Abstract : Anger is a significant human emotion with far‐reaching implications for individuals and relationships. We propose a transactional model of anger that highlights its relational relevance and potentially positive function, in addition to problematic malformations. By evolutionary design, physical, self‐concept, or attachment threats all similarly trigger diffuse physiological arousal, psychologically experienced as anger‐emotion. Anger is first a signaling and motivational system. Anger is then formed to affirming, productive use or malformed to destructive ends. A functional, prosocial approach to anger organizes it for protective and corrective personal and relational adaptation. In our model, threat perception interacts with a person's view of self in relation to other to produce helpful or harmful anger. Inflated or collapsed views of self in relation to other produce distinct manifestations of destructive anger that are harmful to self, other, and relationship. Conversely, a balanced view of self in relation to other promotes constructive anger and catalyzes self, other, and relationship healing. Clinical use of the model to shape healing personal and relational contact with anger is explored.